The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
CALL Communities and Culture – Short Papers From EUROCALL 2016 2016
DOI: 10.14705/rpnet.2016.eurocall2016.557
|View full text |Cite
|
Sign up to set email alerts
|

Can a ‘shouting’ digital game help learners develop oral fluency in a second language?

Abstract: This study examines the development of oral fluency in a Computer-Mediated Communication (CMC) environment that uses a 'shouting' digital game as a pedagogical tool: Spaceteam ESL 4. Spaceteam ESL is a game for mobile devices that involves time-sensitive aural exchanges among players (English learners), with great potential to promote fluency development (via speed) in a non-threatening environment (mediated by the game, a CMC tool). 20 high-beginner/low-intermediate English as a Second Language (ESL) learners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The result of the study coincides with the findings of BavaHarji, Gheitanchian, and Letchumanan (2014), Gashan and Almohaisen (2014), Göktürk (2016), Grimshaw, Cardoso, and Waddington (2016), Abd Al Galil (2019), Cadena-Aguilar, and Ortega-Cuellar, and Cadena-Aguilar (2019). These studies suggested new treatments for oral fluency problems, based on using modern strategies/techniques or adopting another language skill, and these treatments proved to be effective.…”
Section: Discussionsupporting
confidence: 89%
“…The result of the study coincides with the findings of BavaHarji, Gheitanchian, and Letchumanan (2014), Gashan and Almohaisen (2014), Göktürk (2016), Grimshaw, Cardoso, and Waddington (2016), Abd Al Galil (2019), Cadena-Aguilar, and Ortega-Cuellar, and Cadena-Aguilar (2019). These studies suggested new treatments for oral fluency problems, based on using modern strategies/techniques or adopting another language skill, and these treatments proved to be effective.…”
Section: Discussionsupporting
confidence: 89%
“…Other individual differences such as L2 speaking anxiety may decrease through the use of gamified language learning apps (e.g., [11]), while willingness to engage in a task may increase [12]. Additionally, McCarty et al [10] found that mobile devices may be more effective at holding students' attention than tasks completed on a computer, as students are not as likely to multitask; for example, completing a task on a computer allows students to easily switch between windows or tabs, whereas an app covers the entire screen of a mobile device.…”
Section: Teacher-designed Mobile-assisted Language-learning Materialsmentioning
confidence: 99%
“…Twenty-first century technology and language learning practices have continued to provide unique opportunities for language learners, ranging from webcam conversations (e.g., [26]) to interactions in gamified learning spaces (e.g., [11,24]). However, given that CALL is a young discipline primarily grounded in the humanities, an alternative theoretical framework to CALL can be adapted from applied sciences, particularly engineering.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%